2021
DOI: 10.1155/2021/9961145
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy of Ultrasound-Guided High-Voltage Long-Duration Pulsed Radiofrequency for Pudendal Neuralgia

Abstract: Pudendal neuralgia (PN) is a complex disease with various clinical characteristics, and there is no treatment showing definite effectiveness. This study is aimed at evaluating the clinical efficacy of ultrasound-guided high-voltage long-duration pulsed radiofrequency (PRF) for PN. Two cadavers (one male, one female) were dissected to provide evidence for localization of the pudendal nerve. Patients diagnosed as PN who failed or were intolerant in regular medication were screened for diagnostic local anesthesia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…In one study, the success rate of repeated PRF after long-term follow-up was 89% [13], similar to the success rate of 92.1% described by Fang et alin a randomized controlled trial with only 3 months of follow-up [14]. Moreover, high-voltage long-term PRF treatment can relieve the pain of patients with pudendal neuralgia and improve their quality of life by prolonging sitting time without significant serious adverse events [15]. In addition, a retrospective study included 88 adult PN patients whose VAS standardized pain scores were significantly reduced by more than 70% within 3 days after treatment (short term) in both the nerve block and PRF groups.…”
Section: Pudendal Neuralgiasupporting
confidence: 61%
“…In one study, the success rate of repeated PRF after long-term follow-up was 89% [13], similar to the success rate of 92.1% described by Fang et alin a randomized controlled trial with only 3 months of follow-up [14]. Moreover, high-voltage long-term PRF treatment can relieve the pain of patients with pudendal neuralgia and improve their quality of life by prolonging sitting time without significant serious adverse events [15]. In addition, a retrospective study included 88 adult PN patients whose VAS standardized pain scores were significantly reduced by more than 70% within 3 days after treatment (short term) in both the nerve block and PRF groups.…”
Section: Pudendal Neuralgiasupporting
confidence: 61%
“…However, the ultrasound-guided PRF of the pudendal nerve combined with GIB is used in PN, but randomized controlled trials are lacking. In the above studies, the PRF parameters were set as follows: temperature ranging from 42 ℃ to 45 ℃ with a duration from 120 to 900 s. Although the high-voltage long-duration PRF mode shows better improvement in PN [ 12 ], based on our clinical experience and to avoid discomfort, PRF will be administered at 42 ℃ for 480 s in our study. Our primary outcome will be the efficacy of PRF combined with GIB for the long-term improvement of PN.…”
Section: Discussionmentioning
confidence: 99%
“…Fang et al [ 10 ] showed that pudendal nerve PRF combined with PNB provides longer-lasting pain relief and alleviates depression in patients compared with PNB. Ji et al [ 12 ] found that PN was alleviated after 6 months in 88.9% of the patients who received ultrasound-guided high-voltage long-duration PRF. At long-term follow-up (ranging from 2.3 years to 8.8 years), Krijnen et al found that 89% of patients who received repeated PRF with a median interval duration of 3 months between two sessions described their condition as “(very) much better” [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study compared radiofrequency ablation with standard pudendal nerve blocks in 88 patients with pudendal neuralgia. It found rough equivalency in pain relief out to 30 days but improved symptoms with pulsed radiofrequency therapy extending from one to three months [16,17]. Analogous to radiofrequency ablation, cryotherapy of the pudendal nerve is also a promising modality, based on a recent case series, which reported an average reduction in pain of 60% for up to six months after the procedure [18].…”
Section: Discussionmentioning
confidence: 99%